(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the modern democratic image of New Uzbekistan is being created, and the socio-cultural technologies of the strategic path chosen to raise the country to a new stage of development can be partially imagined. The noble aspirations of the Uzbek people related to the creation of the foundations of the New Renaissance period, the most important tasks in the process of their implementation are revealed from a socio-philosophical point of view.